DAMPAK PEMBERIAN INSENTIF PAJAK DAN TAX ALLOWANCE ATAS INVESTASI DAN RASIO PAJAK DI INDONESIA (Media Riset Akuntansi, 2022)
This study aims to analyze the impact on investment and tax ratios in Indonesia after the issuance of the Minister of Finance Regulation Number 150/PMK.010/2018 concerning tax holidays and Government Regulation Number 78 of 2019 concerning tax allowances. The research method used is descriptive qualitative with data collection techniques in the form of archive studies. This study uses secondary data sources taken from data sources published by government agencies and non-governmental institutions of the Indonesian state regarding tax incentives, investment and tax ratios. The results of this study indicate that after the implementation of the tax holiday and tax allowance policies, investment in Indonesia has increased. However, the implementation of tax holidays and tax allowances has not been able to increase the tax ratio in Indonesia because the provision of income tax reductions and exemptions affects tax revenue which has a direct impact on the tax ratio in Indonesia.